ANALISIS KEPEMIMPINAN SPIRITUAL AGAMA BUDDHA: STUDI KASUS PANDITA MAJELIS BUDDHAYANA INDONESIA - Eko Siswoyo (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2026)
This study aims to examine the nature of spiritual leadership among panditas of Majelis Buddhayana Indonesia (MBI) by exploring its forms, challenges, and impacts on Buddhist communities amid social change and technological development. Employing a qualitative descriptive approach, data were collected through online questionnaires distributed to Buddhist followers and in-depth interviews with two key informants: Romo Hendri Gunawan Chandra and Iskandar, Chairperson of the MBI Pandita Council. The findings reveal that spiritual leadership among MBI panditas is primarily characterized by moral exemplarity, empathetic relationships, and service-oriented leadership. Leadership legitimacy is derived not from formal authority, but from personal integrity and consistency in embodying Buddhist values in everyday life. Major challenges faced by panditas include changes in followers’ characteristics—particularly among younger generations—the digitalization of religious life, and the expanding social roles expected of religious leaders in a plural society. The discussion demonstrates that the spiritual leadership of MBI panditas aligns with spiritual leadership theory and servant leadership, while also possessing a strong normative foundation in Buddhist teachings, particularly the concepts of kalyāṇamitta and the Dasa Raja Dhamma. Furthermore, panditas’ adaptive responses to technological change can be understood as forms of upāya (skillful means), enabling spiritual guidance to remain relevant without compromising doctrinal depth. The impacts of spiritual leadership are evident in followers’ character transformation, enhanced spiritual awareness, and strengthened community engagement. This study concludes that the spiritual leadership of MBI panditas is transformative, context-sensitive, and plays a significant role in sustaining Buddhist communal life in contemporary Indonesia.